Formulasi Sediaan Lipstik Menggunakan Pewarna Alami Kopigmentasi Biji Kesumba Keling (Bixa orellana L.) Dengan Angkak Merah Sebagai Pewarna - Salman Salman; Muhammad Iskandar; Sudewi Sudewi; Meutia Indriana (Journal of Pharmaceutical and Sciences, 2023)
Background; appearance is the most common thing to pay attention to, especially among women. Cosmetics are preparations that can improve appearance, one of which is lipstick. Lipstick has the main components, namely wax, oil and dye. One of the natural dyes that can be used as cosmetic dyes are annatto (Bixa orellana L.) and red yeast rice seeds. However, the use of natural dyes in cosmetics has an unstable color. The purpose of this study was to stabilize the dye from annatto (Bixa orellana L.) with red yeast rice seeds using the copigmentation method. Methods; in this study, a maceration process was carried out to obtain extracts from annatto (Bixa orellana L.) and red yeast rice seeds with a ratio of 1:10 (w/v). Then mixed with the thick extract of annatto (Bixa orellana L.) with red yeast rice as a coloring agent, formulated in a ratio of 1:1, 1:2, 2:1 and 2:2. Then the physical quality test of the lipstick preparation was carried out which included homogeneity test, melting point test, lipstick strength test, stability test, smear test, and irritation test. Result; the results showed that the Annatto (Bixa orellana L.) with red yeast rice in the form of copigmentation can be formulated into lipstick preparations with poor homogeneity results. All lipstick preparations meet the requirements of the melting point test, strength test, stability test, smear test, irritation test. The formula with a ratio of 1:2 (F2) is the most preferred preparation by volunteers because it has a good color, smell and texture.